KAJIAN DAMPAK KEBIJAKAN PENUTUPAN LOKALISASI TELEJU OLEH PEMERINTAH KOTA PEKANBARU - Zainuddin, M. (Nakhoda: Jurnal Ilmu Pemerintahan, 2016)
This research to analyze the impact of closure policy Teleju brothel by Pekanbaru govermentin 2010. Guidelines for works are Pekanbaru Local Regulations No. 12 of 2008 on Social Order-liness. Closure this brothel inflicts positive and negative impact for society.The research wasconducted to obtain early stage formula for the government to take action against the prostitu-tion activities. This research uses policy research approach with a qualitative method, becausein prostitution activities and prohibition by goverment is an assessment that needs to be done byanalyzing documents and unstructured interview.The results showed that after the closing of the Teleju brothel have an impact on the deploy-ment of a prostitution and affect the economy of the surrounding residents. Government seeksto tackle prostitution in Pekanbaru by moving the brothel, conduct regular raids and providetraining. The effort is considered to be less than the maximum because the handling is not basedon the root of the problem and not programmed properly. There are several causes of failure ofgovernment to overcome the prostitution problem in Pekanbaru, including: policy content isless focus on the prostitution problem, the government did not proceeds with data, lack of finan-cial support, contra productive programs between local government with the police and TNI,and the policy object is difficult to be given understanding.